Odpowiedzi

2010-02-13T21:09:41+01:00
27=4x³-12x²+9x
27=x(4x²-12x+9)

x=27


delta= 144- 4*4*9= 0
x0= -b/2a
x₀= 12/8
x=3/2

b)P(x)=4x³-12x²+9x = w(x)=x(ax+b)²
x(x)= ax²+xb²
3 2 3
Najlepsza Odpowiedź!
2010-02-13T21:14:52+01:00
A. 4x^3-12x^2+9x=27
4x^3-12x^2+9x-27=0
4x^2(x-3)+9(x-3)=0
(4x^2+9)(x-3)=0
4x^2+9=0 LUB x-3=0
brak rozw. x=3

b. L=4*x^3-12*x^2+9*x
P=x(a*x^2+ab*x+b^2)=a*x^3+ab*x^2+b^2*x
skoro L=P, tp:

a*x^3=4*x^3 czyli a=4
-12*x^2=ab*x^2 czyli -12=ab, -12=4b, b=-3
co zgadza się z b^2*x=9*x (tu możliwe jeszcze b=3 niezgodne z powyższym, więc wykluczamy)
2 4 2